Problems of Literacy and Numeracy Skills of Students at the Elementary School Level - Dewi Nurlita Kurniawati; Mohamad Ali; Mutohharun Jinan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to examine the problems in the literacy and numeracy skills of students at the elementary school level and the factors that affect them in the learning process. This study uses a qualitative approach with a descriptive type of research. Data were collected through learning observations, in-depth interviews with classroom teachers and students, and documentation studies on learning outcomes and learning tools. Data analysis techniques are carried out through the stages of data reduction, data presentation, and conclusion drawing by applying data validity tests through triangulation of sources and techniques. The results of this study show that the literacy and numeracy skills of elementary school students are still relatively low, especially in the aspects of reading comprehension, mathematical reasoning, and the application of concepts in the context of daily life. The main causative factors include low interest in reading, limited variety of learning methods, lack of use of innovative learning media, and lack of support for the learning environment at home. This research has an originality value in mapping literacy and numeracy problems comprehensively based on the context of learning in elementary schools. The findings of this research are expected to be the basis for educators and policy makers in designing learning strategies that are more contextual, innovative, and oriented towards strengthening students' literacy and numeracy skills in a sustainable manner.